Pelatihan Literasi Pengelolaan Keuangan Digital “Si APIK” Bagi UMKM di Kota Palembang - Ruth Samantha Hamzah; Yusnaini; Relasari; Efva Octavina Donata Gozali (Sriwijaya Accounting Community Services, 2023)
Limited knowledge about the process of recording digital transactions is a major factor faced by MSME in the technological era. The application-based financial transaction recording needs to be understood by MSME owners because it overcomes problems in recording financial transactions. This activity proves that by giving training, MSMEs could understand about financial statement, financial reporting flows, financial reporting applications, and financial reporting flows using "Si Apik". It is shown by an increase of 53 percent of participants understanding the flow of financial reporting using “Si Apik” after the training.